The Possibility of Applying Lean Operation in Industrial Companies Applied Research in the General Company for Leather Industries - Atheer Ali Abdulkadhim; Khawla Hussein Hamdan (Journal of Madenat Alelem University College, 2021)
The research aims to identify lean operation and tools and how to apply them, as well as to get rid of all non-value-added activities of waste of time and resources, as well as to identify the practical results obtained after the application of lean operation techniques as well as the amount of financial savings that will be obtained in the case of application. Where the research problem was the result of major developments in the business environment and rapid changes in customer demands has become the need to provide modern systems to meet these requests as the traditional systems are not adapted to the current changing environment and must adopt modern systems appropriate to change quickly response to customers’ requests, Where he reached many conclusions, the most important when applying the manufacturing efficiency cycle shows that the efficiency ratio in traditional systems is (40%) and this is a weakness indicator in the company because the amount (60%) represents activities that do not add any value to the product and borne by the company as it reaches searching for many recommendations, the most important of which is the need to implement lean operation , which helps to delete activities that are not value added to the product, which represents a burden borne by the company where the efficiency of manufacturing has become by (71%) when the application of lean operation techniques of just in time.